Role of Age in the Spread of Influenza, 2011–2019: Data From the US Influenza Vaccine Effectiveness Network. Issue 3 (16th July 2021) - Griggs, Eric P; Flannery, Brendan; Foppa, Ivo M; Gaglani, Manjusha; Murthy, Kempapura; Jackson, Michael L; Jackson, Lisa A; Belongia, Edward A; McLean, Huong Q; Martin, Emily T; Monto, Arnold S; Zimmerman, Richard K; et al.
Abstract: Intraseason timing of influenza infection among persons of different ages could reflect relative contributions to propagation of seasonal epidemics and has not been examined among ambulatory patients. Using data from the US Influenza Vaccine Effectiveness Network, we calculated risk ratios derived from comparing weekly numbers of influenza cases prepeak with those postpeak during the 2010–2011 through 2018–2019 influenza seasons. We sought to determine age-specific differences during the ascent versus descent of an influenza season by influenza virus type and subtype. We estimated 95% credible intervals around the risk ratios using Bayesian joint posterior sampling of weekly cases. Our population consisted of ambulatory patients with laboratory-confirmed influenza who enrolled in an influenza vaccine effectiveness study at 5 US sites during 9 influenza seasons after the 2009 influenza A virus subtype H1N1 (H1N1) pandemic. We observed that young children aged <5 years tended to more often be infected with H1N1 during the prepeak period, while adults aged ≥65 years tended to more often be infected with H1N1 during the postpeak period. However, for influenza A virus subtype H3N2, children aged <5 years were more often infected during the postpeak period. These results may reflect a contribution of different age groups to seasonal spread, which may differ by influenza virus type and subtype.